Interspecific interference competition between two field cricket species. Issue 3 (29th July 2019) - Tajima, Shingo; Yamamoto, Kyohei; Kuriwada, Takashi
Abstract: Species interactions, such as interspecific competition, determine population dynamics and community structure. In a park of Amami Oshima Island, Japan, two field cricket species Teleogryllus occipitalis (Audinet‐Serville) (Gryllidae) and Loxoblemmus equestris Saussure (Gryllidae) are dominant species. We examined the interference competition at the nymph and adult stages in the two crickets under controlled laboratory conditions. Survival and emergence rates of T. occipitalis were not affected by the density of L. equestris, whereas survival and emergence rates of L. equestris decreased as the density of T. occipitalis increased. These results showed that T. occipitalis was competitively superior over L. equestris in species interactions. We discuss inconsistency between the results and coexistence of these two species under field conditions. Abstract : Survival and emergence rates of Teleogryllus occipitalis not affected by density of Loxoblemmus equestris, but survival and emergence rates of L. equestris decreased as density of T. occipitalis increased. Emergence rates of both species were higher in nymphs fed a high‐quality diet than a low‐quality diet. These two field crickets coexist in nature despite the asymmetrical interspecific interaction.